Creole: a contested, polysemous term. Issue 15 (8th December 2017) - Cope, Michael R.; Schafer, Mark J.
ABSTRACT: In this paper, we critically examine the polysemous term, creole, used at different times and various geographical areas to describe diverse identities, languages, peoples, ethnicities, racial heritages, and cultural artefacts. Our objective is twofold: (1) to describe the historically contested nature of the term and its connection to broader trends in defining race in the United States and (2) to suggest that a deeper understanding of racially situated terms such as creole can help to highlight the contextualized character of racial/ethnic divisions, trends, and labels. Our analysis shows that in many ways the Creole people of the United States Gulf Coast Region truly represent the "melting pot" mantra in espoused American ideology and exemplify a direct challenge to bygone racial ideologues which espoused the idea that mixing produces hybridized, impudent, weak, and sickly offspring.